2018
DOI: 10.1007/978-3-319-89960-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Strategy Representation by Decision Trees in Reactive Synthesis

Abstract: Graph games played by two players over finite-state graphs are central in many problems in computer science. In particular, graph games with ω-regular winning conditions, specified as parity objectives, which can express properties such as safety, liveness, fairness, are the basic framework for verification and synthesis of reactive systems. The decisions for a player at various states of the graph game are represented as strategies. While the algorithmic problem for solving graph games with parity objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…Fourthly, DT can use much wider class of predicates, compared to single bit tests for a bit representation in a BDD. This final point is also a reason (together with the smaller size) why DT is a more understandable representation than a BDD [8,9]. We also illustrate this point on a case-study in Remark 1.…”
Section: Comparing Dts To Binary Decision Diagramsmentioning
confidence: 71%
See 3 more Smart Citations
“…Fourthly, DT can use much wider class of predicates, compared to single bit tests for a bit representation in a BDD. This final point is also a reason (together with the smaller size) why DT is a more understandable representation than a BDD [8,9]. We also illustrate this point on a case-study in Remark 1.…”
Section: Comparing Dts To Binary Decision Diagramsmentioning
confidence: 71%
“…In the context of verification, MDPs are often represented using variants of (MT)BDDs [20,29,40], and strategies by BDDs [56]. Learning a compact decisiontree representation of a strategy has been investigated in [38] for the case of body sensor networks, in [8] for finite (discrete) MDPs, and in [9] for finite games, but only with Boolean variables. Moreover, these decision trees can only predict a single action for a state configuration whereas in this work, we allow the trees to predict more than one action for a single configuration.…”
Section: Our Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a data structure to represent strategies, there are some desirable properties, which are as follows: (a) succinctness, i.e., small strategies are desirable, since smaller strategies represent efficient controllers; (b) explanatory, i.e., the representation explains the decisions of the strategies. While one standard data structure representation for strategies is binary decision diagrams (BDDs) [2,13], recent works have shown that decision trees [46,40] from machine learning provide an attractive alternative data structure for strategy representation [9,11]. The two key advantages of decision trees are: (a) Decision trees utilize various predicates to make decisions and thus retain the inherent flavor of the decisions of the strategies; and (b) there are entropy-based algorithmic approaches for decision tree minimization [46,40].…”
Section: Introductionmentioning
confidence: 99%